De afzetting van Lumumba Door Kasavubu, enkele grondwettelijke beschouwingen - Beke, Dirk (Afrika Focus, 2000)
Shortly after the independence of the Congo, the political crisis engendered by the conflict between President Kasavubu and Prime Minister Lumumba was accompanied by a serious constitutional crisis. The first Congolese constitution was almost a complete imitation of the Belgian constitution. It established a parliamentary regime with a politically accountable Prime Minister and a non-accountable President as Head of State. The confusing rubric that 'The Head of State appoints and dismisses the Prime Minister' was quickly misused by national and international opponents of Lumumba to persuade Kasavubu to remove him from power. A full and contextual analysis of the constitution, however, shows that dismissal is linked to several other formal procedures and political conditions. Every presidential decision, including the dismissal of the Prime Minister and of Ministers, has to be countersigned by a Minister. Furthermore, it can be deduced clearly from the whole constitutional model that dismissal of the Prime Minister can only take place when the government has been outvoted in parliament. The conclusion is that, in contradiction to the contrived interpretations of some advisers and Belgian jurists, the deposition of Lumumba was unconstitutional. At any rate, Kasavubu's unconstitutional act seriously damaged Lumumba's political position and placed him in a difficult situation of legal defence against it. KEY WORDS : Congo, Constitution, Lumumba, Politics